Business ethics. - Shaw, William H., 1948-; Miller, Dale E., 1966- (Cengage, 2025)
Combining text, thought-provoking case studies and supporting Web resources, this title provides a comprehensive survey of business ethics which will be of interest to undergraduates at all levels with little or no philosophical background.